The role of Escherichia coli type III secretion system 2 chaperone protein ygeG in pathogenesis of avian pathogenic Escherichia coli. (November 2021) - Yin, Lei; Li, Qianwen; Wang, Zeping; Tu, Jian; Shao, Ying; Song, Xiangjun; Pan, Xiaocheng; Qi, Kezong
Abstract: The Escherichia coli type III secretion system 2 (ETT2) is present in most E. coli strains, carries a 29.9-kb ETT2 pathogenicity island (PAI) and is involved in the virulence of avian pathogenic Escherichia coli (APEC). A chaperone protein is essential for the bacterial secretion system, but the function of the ETT2 chaperone protein has not been determined. This study showed that ygeG had sequence homology with the identified bacterial chaperone protein and it possessed tetratri-copeptide repeats (TPR) containing protein. To investigate the role of ygeG in the ETT2 of APEC, ygeG mutant and complemented strains were constructed and characterized. Inactivation of ygeG had no effect on APEC growth, but significantly promoted biofilm formation, and the adherence to and invasion of DF-1 cells, especially the survival abilities in specific-pathogen-free (SPF) chicken sera serum. Analysis of the role of ygeG in chicken infection models revealed that the deletion of ygeG increased bacterial virulence. RNA Sequencing (RNA-Seq) analyses comparing the APEC wild type and the ygeG mutant indicated that multiple genes encoding biofilm formation, outer membrane proteins, fimbrial genes and virulence effector protein genes were regulated by ygeG . These results revealed the role of ygeG as a chaperone protein that affected the virulence and pathogenicity of APEC. Highlights: We predicted and identified the new Escherichia coli type III secretion system 2 molecular chaperone ygeG . We have demonstrated ygeG plays an important role in regulating the pathogenicity of avian pathogenic Escherichia coli . We identified the candidate genes that ygeG might regulated by transcriptomics analysis.